PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) (Studi Kasus di Kecamatan Padang Gelugur Kabupaten Pasaman) - Fatma Yuliza; Tartila Devy (CV. Adiba Aisha Amira, 2025)
The purpose of this study was to determine the effect of taxpayer awareness and knowledge on taxpayer compliance in paying land and building tax in rural and urban areas in Padang Gelugur District, Pasaman Regency. The population of this study was 12,845 land and building taxpayers in rural and urban areas in Padang Gelugur District. The sampling technique used was propositional sampling using the Solvin formula for 99 people. The analysis method used was multiple linear regression analysis and descriptive analysis using IBM SPSS 26 V software. Interviews and questionnaires were used in the data collection process. The findings of the study indicate that (1) taxpayer knowledge has a significant effect on land and building taxpayer compliance in rural and urban areas. (2) Land and building taxpayer compliance in rural and urban areas is not influenced by taxpayer awareness. (3) Land and building taxpayer compliance in rural and urban areas is significantly influenced by taxpayer awareness and taxpayer knowledge simultaneously.